Implementation of KH. Hasyim Asy’ari’s Pedagogical Model and Its Implications for Arabic Language Learning in Madrasah Diniyah - Sifa Mahfudoh; Sofyan Sauri; Mad Ali; Fairin Azizah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the implementation of KH. Hasyim Asy’ari’s pedagogical model and its implications for Arabic language learning in madrasah diniyah through a systematic literature review (SLR) approach and bibliometric analysis using VOSviewer. Islamic education, which is rooted in the pesantren tradition, places character formation at the core of the learning process, as formulated in the book Adabut Ta’lim wal Muta’allim. This study applies the PRISMA protocol with a publication range of 2021–2026 and identifies 20 articles that meet the inclusion criteria. The results show that KH. Hasyim Asy’ari’s pedagogical model is characterized by an emphasis on educator ethics, teacher–student relationships grounded in adab, and the integration of knowledge mastery with personality formation. VOSviewer visualization identifies five main clusters: pesantren and kitab kuning as the pedagogical basis, Islamic education reform, the conceptual dimension of educational thought, the national context, and Arabic language learning. The findings indicate a shift from philosophical studies toward practical implementation and methodological innovation, particularly in increasingly adaptive Arabic language learning. The implications of this study show that traditional methods such as sorogan and bandongan remain relevant, but need to be integrated with communicative approaches, learning technology, and contextual strategies to improve Arabic language competence. This study affirms that KH. Hasyim Asy’ari’s pedagogical model remains an important foundation for developing Arabic language learning rooted in ethical values while remaining open to modern educational innovation.